2015
DOI: 10.1016/j.placenta.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of inflammation and apoptosis in initiation of mid-gestational abortion in malaria-infected C57BL/6 and A/J mice

Abstract: Introduction Plasmodium chabaudi AS-infection in pregnant A/J and C57BL/6J mice results in mid-gestational pregnancy loss. Although associated with increased systemic and placental pro-inflammatory responses and coagulopathy, the molecular mechanisms that underlie poor pregnancy outcomes in these mice are not yet fully understood. This study investigates the relationships between inflammation, apoptosis and malaria-induced pregnancy loss. Methods Infection with Plasmodium chabaudi AS in early murine pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 64 publications
(132 reference statements)
0
17
1
Order By: Relevance
“…Given that excessive or uncontrolled production of HNE interferes with cellular signaling, and a role in the pathogenesis of several diseases, including severe malaria, has been suggested (44), placental lipid peroxidation may be central to PM-associated compromise of pregnancy, Indeed, at very high levels, HNE reportedly induces apoptosis or necrosis (45). Although we previously demonstrated that the former is unlikely to mediate embryo loss in infected B6 mice (17), necrotic placental damage is observed (D. Sarr, J. Ecker, J.M. Moore, unpublished observations).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Given that excessive or uncontrolled production of HNE interferes with cellular signaling, and a role in the pathogenesis of several diseases, including severe malaria, has been suggested (44), placental lipid peroxidation may be central to PM-associated compromise of pregnancy, Indeed, at very high levels, HNE reportedly induces apoptosis or necrosis (45). Although we previously demonstrated that the former is unlikely to mediate embryo loss in infected B6 mice (17), necrotic placental damage is observed (D. Sarr, J. Ecker, J.M. Moore, unpublished observations).…”
Section: Discussionmentioning
confidence: 89%
“…Plasma and tissues were collected as described below. Mice were dissected for evaluation of embryo status and isolation of tissues as previously described (14, 15, 17, 18). Briefly, resorptions or nonviable embryos were identified by their necrotic and/or smaller size compared with viable normal embryos as they appear in uninfected pregnant (UP) mice.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations